2018
DOI: 10.1590/0366-69132018643722429
|View full text |Cite
|
Sign up to set email alerts
|

Study of equilibrium and kinetic adsorption of rhodamine B onto purified bentonite clays

Abstract: Currently, the removal of contaminants such as wastewater dye has become an essential task. In view of this, improving the performance of the adsorbents in order to improve the adsorption technique and reduce the total cost of the adsorption process is of great interest to the industrial sector. This study investigated the adsorption process of natural and purified bentonite clay adsorbents, using rhodamine B in an aqueous media. Rhodamine B is very toxic to aquatic organisms and may cause long-term adverse ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…This loss can be attributed to the decomposition of calcite present in bentonite (Fig. 2b) into oxides (CaCO 3 gCaO+CO 2 ) [27]. The total mass loss of bentonite was 18.4%.…”
Section: Resultsmentioning
confidence: 97%
“…This loss can be attributed to the decomposition of calcite present in bentonite (Fig. 2b) into oxides (CaCO 3 gCaO+CO 2 ) [27]. The total mass loss of bentonite was 18.4%.…”
Section: Resultsmentioning
confidence: 97%
“…However, the pseudo-second-order model showed better R 2 values (near 1), indicating a better description of the adsorption kinetics. From the concept of this model, it is possible to infer that the limitation rate of the dye molecules adsorption in the clay occurs mainly through chemisorption [36,37,86,87]. Therefore, the second-order model is the most indicated to describe the adsorption mechanism, possibly due also to the interaction between the dye molecules and the new sites generated on the surface.…”
Section: Adsorption Testsmentioning
confidence: 99%
“…Table 1 summarizes the adsorption amount and rate constants. The adsorption curve of the dye mainly follows pseudo-second-order kinetics ( Figure 5 b) [ 42 ]. The adsorption amount of rhodamine B for two hours showed that the q e of TiO 2 @HNT/Alcap was 0.1704, which was about 1.7 times higher than that of the bare alginate capsules (q e 0.1026).…”
Section: Resultsmentioning
confidence: 99%